THE INFLUENCE OF ONLINE CUSTOMER REVIEW, LIVE TIKTOK, ON PURCHASE DECISION OF SOMETHINC PRODUCTS WITH CUSTOMER TRUST AS A MEDIATION VARIABLE ON TIKTOK SOCIAL MEDIA - Vanysa Stefani; Erna Listiana; Nur Afifah; Harry Setiawan; Ana Fitriana (SEAN Institute, 2023)
The internet has experienced rapid progress, as has business developing to reach the era of the internet or online media. This research aims to test the influence of online customer reviews live streaming on consumer purchase decisions on certain products through customer trust on TikTok social media. This type of research is causal associative by distributing questionnaires to 200 respondents who live in Indonesia. The data was analyzed using SEM with AMOS 24 software. The results of this research show that all hypotheses are accepted, namely, online customer reviews and live streaming have a positive and significant effect on customer trust and purchase decisions for some products. Apart from that, customer trust can play a mediating role that has a positive and significant influence on online customer reviews and live streaming on purchasing decisions for certain products.